Manipulative impact of implicit communication: : A comparative analysis of French, Italian and German political speeches - Cominetti, Federica; Cimmino, Doriana; Coppola, Claudia; Mannaioli, Giorgia; Masia, Viviana (Linguistik Online, 2023)
This paper presents the application of a quantitative model for measuring the impact of manipulative implicit linguistic strategies on a small comparable corpus of Italian, German and French political discourses. The aim is to show the cross-linguistic applicability of the model, originally developed and put to test on Italian. Furthermore, the analysis allows a quantitative and qualitative comparison of the three comparable corpora: some statistical correlations and tendencies in the frequency and type of linguistic implicit strategies are presented and put in relation not only with the language, but also with the political orientation of the speaker and with other parameters (context, subject, rhetorical style). Results show that the model can be applied to multiple languages and that inter- and intra-linguistic tendencies in the use of manipulative implicit linguistic strategies can be appreciated.